Records Committee review for rare bird sighting of Lesser Black-backed Gull at Coralville Dam, 1993 - Pinkston, Randall, 1956-et al (1993)
Records Committee review for a Lesser Black-backed Gull at Coralville Dam in Johnson County, IA on December 11, 1993. Includes a record review document with votes and three documentation forms submitted to the committee. Epson - sheet feed